Nonparametric identification in panels using quantiles - Victor Chernozhukov; Ivan Fernández-Vál; Stefan Hoderlein; Hajo Holzmann; Whitney Newey (Centre for Microdata Methods and Practice (cemmap), 2013)
This paper considers identification and estimation of ceteris paribus effects of con- tinuous regressors in nonseparable panel models with time homogeneity. The effects of interest are derivatives of the average and quantile structural functions of the model. We find that these derivatives are identified with two time periods for 'stayers', i.e. for individuals with the same regressor values in two time periods. We show that the identifi- cation results carry over to models that allow location and scale time effects. We propose nonparametric series methods and a weighted bootstrap scheme to estimate and make inference on the identified effects. The bootstrap proposed allows uniform inference for function-valued parameters such as quantile effects over a region of quantiles or regressor values. An empirical application to Engel curve estimation with panel data illustrates the results.
Keywords: 330; Panel data; nonseparable model; average effect; quantile effect; Engel curve